2009
DOI: 10.5737/1181912x193117121
|View full text |Cite
|
Sign up to set email alerts
|

Women’s decision-making needs related to treatment for recurrent ovarian cancer: A pilot study

Abstract: The purpose of this pilot study was to describe the decision-making needs of women with ovarian cancer related to treatment of recurrent disease.Design: A retrospective, cross-sectional needs assessment was conducted. Data were collected using face-to-face interviews and analyzed using content analysis. Group, 2006). Given the lack of one superior treatment, decisions should be based on patient preferences (O'Connor et al., 2004). ResultsThere is evidence that women want more information related to ovarian ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Only two of six patients described selecting a specific treatment option. This finding is congruent with previous findings in the literature that suggest the extent to which women with ovarian cancer participate in treatment decision making varies [ 23 , 24 ]. Patients in the current study reported that the urgency with which they started treatment limited the extent to which they participated in shared decision making.…”
Section: Discussionsupporting
confidence: 92%
“…Only two of six patients described selecting a specific treatment option. This finding is congruent with previous findings in the literature that suggest the extent to which women with ovarian cancer participate in treatment decision making varies [ 23 , 24 ]. Patients in the current study reported that the urgency with which they started treatment limited the extent to which they participated in shared decision making.…”
Section: Discussionsupporting
confidence: 92%
“…Physical limitations included active or unresolved medical problems impairing decision making (e.g., sedating medications, unresolved pain or weakness, or disrupted sleep/wake cycle) ( n = 6; 13%). 30,35,43,51,55,58 Cognitive limitations included cognitive impairment or memory problems ( n = 2; 4%). 30,58 Emotional limitations were distress, fear, anxiety, worry, uncertainty, frustration, and feeling out of control ( n = 4; 9%).…”
Section: Resultsmentioning
confidence: 99%
“…50 This relationship need was further elaborated in other studies as needing clear communication, 39,41,45 mutual respect, 39,45 empathy and compassionate care, 36,39 and honesty. 36,38,39,51 Two new manifestations of difficult decisional roles emerged regarding families ( Table 7). The first one was coded as difficulty involving family members in decision making, and contributing factors were not wanting to worry their family and inadequate family knowledge of the condition and treatment options.…”
Section: Validation Of Odsf Decisional Needsmentioning
confidence: 99%
“…Our needs assessment questionnaire was based on the needs assessment workbook provided at the University of Ottawa Patient Decision Aids website (13), and used the Ottawa Decision Support Framework, which have face and content validity (14,15). Many studies previously have used this needs assessment survey (16)(17)(18)(19)(20).…”
Section: Methodsmentioning
confidence: 99%